2018
DOI: 10.1111/ejh.13056
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of de novo and secondary myeloid sarcoma: A monocentric retrospective study

Abstract: De novo myeloid sarcoma mostly presented isolated. Lesions were often localized at skin and lymph nodes. Genetic aberrations frequently involved core-binding factor rearrangements in de novo cases and a complex karyotype in secondary cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
(138 reference statements)
2
31
0
Order By: Relevance
“…Similarly, a recent study on 72 patients with MS performed by Claerhout et al . showed that cutaneous MS had a significantly shorter overall survival compared to the other sites ( P = 0.0167) . Goyal et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, a recent study on 72 patients with MS performed by Claerhout et al . showed that cutaneous MS had a significantly shorter overall survival compared to the other sites ( P = 0.0167) . Goyal et al .…”
Section: Discussionmentioning
confidence: 96%
“…16 Similarly, a recent study on 72 patients with MS performed by Claerhout et al showed that cutaneous MS had a significantly shorter overall survival compared to the other sites (P = 0.0167). 17 Goyal et al stratified 746 MS patients based on tumour locations into prognostic groups: good (OS > 30 months: reproductive and digestive system), intermediate (OS = 15-30 months, head/neck, skin/ breast, and kidney/bladder/retroperitoneum/adrenal) and poor (OS < 15 months: nervous system, connective/soft tissue, lymph nodes/spleen, cardiac/mediastinal and bones/joints). 18 Goyal et al hypothesised that reproductive and digestive system MS may have a better prognosis due to earlier symptom onset, while bone MS may indicate onset of bone marrow involvement.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually associated with acute myeloid leukemia (AML), chronic myeloid leukemia (CML), and other myeloproliferative disorders and can present as soft tissue swelling. Granulocytic sarcomas are usually found in skin, bones and lymph nodes. Though difficult to differentiate on the basis of morphology alone, this differential is excluded by normal peripheral blood picture, bone marrow examination and immunophenotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Additional metastasis of the primary, is further associated with a worse prognosis. No optimal treatment protocol is established yet, and a combination of modalities, including surgery and chemotherapy, has been suggested . The role of adrenalectomy for diagnosis and therapy is debatable.…”
Section: Discussionmentioning
confidence: 99%
“…MS most commonly manifests in the skin, subcutaneous tissues, and the lymph nodes. Claerhout et al conducted a case series of 41 patients with de novo MS and 31 patients with secondary disease [19]. Among both cohorts, respectively, they found that MS localized to the skin in 24-25.5% of cases, lymph nodes (18.2-16.0%), gastrointestinal tract [20] (10.9-2.0%), breast (7.3-10.0%), ovary (3.6-0.0%), cervix/urine corpus (1.8-4.0%), bone (3.6-6.0%), and brain (3.6-6.0%).…”
Section: Discussionmentioning
confidence: 99%